It is Always Dry Here: Examining Perceptions about Drought and Climate Change in the Southern High Plains. Issue 7 (3rd October 2019) - Colston, Nicole M.; Vadjunec, Jacqueline M.; Fagin, Todd
ABSTRACT: Drought is defined, experienced, and communicated about in multiple ways. This case study examines individual definitions of drought (timing, impacts, and severity) and attitudes about climate change. Household surveys ( n = 120) were conducted in Cimarron County, Oklahoma and Union County, New Mexico using a stratified random sampling method to select farmers, ranchers, and town residents. Information about drought is primarily communicated between neighbors, friends, and family, as well as media and local governing agencies. Residents perceive the recent drought to be the worst drought on record, regardless of previous drought experiences. Residents reported widespread drought-related impacts on agriculture, environment, and society. Most residents see drought as cyclical and driven by natural causes, rather than human causes. We recommend adaptive drought communication engage more fully with identity, place, and history. Climate information should be presented in a relevant manner to diverse agricultural stakeholders with differing attitudes about climate change, management, and climate information.